HAK PERDATA MASYARAKAT DESA KAYU DUJUNG DALAM PENYELESAIAN PEMECAHAN SERTIFIKAT TANAH KANTOR BADAN PERTANAHAN NASIONAL SINTANG - Stefanus Ngebi (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2022)
Earth is god’s gift of earth. The Land is a vital for human being as sources of human welfare, life and happiness. The rupiah rose to Rp.9,310/9,329 per dollar in the Jakarta interbank spot market on Tuesday morning as investors bought the local unit. It creates a wide range of needs both in individual and in group, both for offices or institutions, provide fertility in the economic needs of food and clothing. People should live in land and building. Therefor, land ownership is important aspect as means to create an ownership of land certificate. the legality of land ownership is necessary in the light of a valid evidence. The only way to prove land ownership of every society is using land certificate. This study is designed in the form of juridical sociological approach. The nature of this study is a descriptive analysis that describes thoroughly the systematic objects of the subject matter. A deed of land issued by the National lands Agency (BPN).Keywords: civil rights, Land certificates